2014
DOI: 10.1021/cm502929m
|View full text |Cite
|
Sign up to set email alerts
|

Microplasma-Based Growth of Biphasic NiFe2O4/NiO Nanogranular Films for Exchange Bias Applications

Abstract: Biphasic, nanostructured NiFe 2 O 4 /NiO films exhibiting exchange bias were synthesized using high-pressure microplasma-based deposition. Organometallic Ni and Fe precursors were dissociated via electron impact in the hollow cathode region of a supersonic plasma jet with oxygen to form a directed flux of Ni and Fe oxide species that were subsequently spray-deposited on SiO 2 /Si substrates to form nanostructured thin films. Exchange bias (H E ) and coercivity (H C ) enhancement were observed for all films con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…With increasing sintering temperature, the size of particles become larger and the NiFe 2 O 4 particles may form ferromagnetic type clusters in NiO matrix as result of which effective coupling among the NiFe 2 O 4 and NiO decreases. Similar types of observations have also been reported [19,33,[60][61][62]. Hence it is clear from the study that relatively larger size NiFe 2 O 4 particles or more ferromagnetic NiFe 2 O 4 phase in the system is not the good choice for the occurrence of EB in this system.…”
Section: Effect Of Sintering Temperaturesupporting
confidence: 85%
See 2 more Smart Citations
“…With increasing sintering temperature, the size of particles become larger and the NiFe 2 O 4 particles may form ferromagnetic type clusters in NiO matrix as result of which effective coupling among the NiFe 2 O 4 and NiO decreases. Similar types of observations have also been reported [19,33,[60][61][62]. Hence it is clear from the study that relatively larger size NiFe 2 O 4 particles or more ferromagnetic NiFe 2 O 4 phase in the system is not the good choice for the occurrence of EB in this system.…”
Section: Effect Of Sintering Temperaturesupporting
confidence: 85%
“…Pebley et al [33] have synthesized nanostructured NiFe 2 O 4 / NiO films using high-pressure microplasma-based deposition by varying Ni molar compositions (x Ni ). These authors reported that the presence of both NiFe 2 O 4 and NiO in the samples prepared with x Ni = 0.49−0.74.…”
Section: Effect Of Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and detailed elsewhere [35]. The MP source consists of a stainless steel capillary tube (i. d.¼500 μm) operating as the cathode and a grounded ring as the anode with Macor insulator.…”
Section: Microplasma Depositionmentioning
confidence: 99%
“…As such, we continually seek to develop general and tunable methods that can easily and rapidly create nanostructured functional materials. For example, atmospheric pressure plasmas [5,6], plasma sprays [7][8][9], and microplasmas [10][11][12][13][14][15][16][17][18][19][20] have shown much promise toward this goal. Extending and adapting such methods in a generic way to different material systems and deposition situations, as well as understanding how plasma operating conditions affect growth processes, is critical for their implementation.…”
mentioning
confidence: 99%